CONSTRUINDO A DISCIPLINA DE PSICOFARMACOLOGIA E APRENDIZAGEM COM ALUNOS DE UM CURSO DE PÓS-GRADUAÇÃO A PARTIR DE CÍRCULOS DE DIÁLOGO E COMPREENSÃO (Revista Contexto & Educação, 2021)
This article aims to reflect on the difficulties faced by students in learning and the factors related to the use of medications, especially in school age. These reflections will be made from the construction of dialogue circles and understanding where each graduate will have the opportunity to bring their experiences in the classroom with their students. The dialogue circles are based on the listening – and within this the presence, attention and silence of each participant. Using this methodology, it was possible to structure the discipline of psychopharmacology and learning taught in the postgraduate course in clinical and institutional neuropsychopedagogy. Through this construction between teachers and students it was possible to explore different areas, including: Pharmacology, neuroscience, Social pedagogy and psychology. We verified that often the use of medications in individuals, especially in childhood and adolescence, occurs wrongly, large quantities, high dosages and often without a correct diagnosis. This concludes that good doses of love, affection and attention can considerably replace the use of these medications. The student must be enchanted by the world, through the space in which he is learning.